Identifying peroxidases and their oxidants in the early pathology of cystic fibrosis. - Thomson, E.; Brennan, S.; Senthilmohan, R.; Gangell, C.; Chapman, A.; Sly, P.; Kettle, A.; Balding, E.; Berry, L.; Carlin, J.; Carzino, R.; de Klerk, N.; et al. (2010)
We aimed to determine whether myeloperoxidase (MPO) is the main peroxidase present in the airways of children with cystic fibrosis (CF) and to assess which oxidants it produces and whether they are associated with clinical features of CF. Children with CF (n=54) and without CF (n=16) underwent bronchoscopy and bronchoalveolar lavage (BAL) for assessment of pulmonary infection and inflammation. BAL fluid was analyzed for MPO, halogenated tyrosines as markers of hypohalous acids, thiocyanate, and protein carbonyls. MPO was the only peroxidase detected in BAL samples from children with CF and its concentration was markedly higher than in controls. Levels of 3-chlorotyrosine and 3-bromotyrosine in proteins were higher in the CF group. They correlated with neutrophils and MPO. The concentration of thiocyanate in BAL samples was below 1μM. Protein carbonyl levels correlated with MPO and halogenated tyrosines in patients with CF. Levels of MPO and halogenated tyrosines were higher in children with infections, especially Pseudomonas aeruginosa, and in the presence of respiratory symptoms. They also correlated with the Kanga clinical score. Our findings suggest that MPO produces hypobromous acid as well as hypochlorous acid in the airways of children with CF and that these oxidants are involved in the early pathogenesis of CF.